The Role of Hadith in Character and Moral Formation and Its Implementation in Strengthening Moral Education - Imam Ali Ishomuddin Haromain; Ahmad Muhammad Tidjani; Abdul Kirom (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This study examines the role of hadith in character education, particularly in shaping the moral values of young Muslims in the era of globalization. The growing moral degradation demands a comprehensive approach rooted in Islamic values. Using library research as the method, the study analyzes selected hadiths alongside relevant academic literature on character education. Findings reveal that hadith plays a significant role in fostering values such as justice, patience, honesty, compassion, empathy, and ethical conduct in worship and daily interactions. The implementation of hadith is not only normative but also practical, as demonstrated by Prophet Muhammad’s exemplary methods in educating his family and companions. Moreover, the family, as the primary educational institution, has a strategic role in instilling moral values through habituation, guidance, and exemplary behavior. Nevertheless, modern challenges such as globalization, popular culture, and limited parental control over technology often undermine children’s character development. Therefore, this study emphasizes that strengthening moral education based on hadith is an effective strategy to address the moral crisis and to nurture a generation with noble character.